The artist's house : from workplace to artwork - Bell, Kirsty; Whitman-Salkin, Leah (Berlin : Sternberg Press, 2013)
Workplaces of Paweł Althamer; Mirosław Bałka; Louise Bourgeois; Marc Camille Chaimowicz; Dominique Gonzalez-Foerster; Katharina Grosse; Edward Krasiński; Mark Leckey; Carlo Mollino; Alice Neel; Gabriel Orozco; Gregor Schneider; Kurt Schwitters; Monika Sosnowska; Frances Stark; Florine Stettheimer; Rirkrit Tiravanija; Danh Vo; Andrea Zittel
boek